2017
DOI: 10.25120/qar.20.2017.3584
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal stone huts along the Georgina River, southwest Queensland

Abstract: This paper reports on the recording of previously unpublished Aboriginal stone hut structures in southwestern Queensland. Located along a tributary of the Georgina River, these 17 structures are typical of the region, being generally circular in plan view, with an average diameter of 5m and a 1m-wide opening consistently positioned to afford protection from prevailing winds. Evidence suggests these structures were roofed with vegetation and, while they pre-date the contact period, appear also to have been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Colonial and post-colonial era Indigenous sites have similar issues (e.g. McNiven et al, 2017;Wallis and Collins, 2013;Wallis et al, 2017). Our results, therefore, provide a successful proof of concept for using quartz OSL to date anthropogenic sediments at archaeological sites of the colonial era (i.e.…”
Section: Resultssupporting
confidence: 55%
“…Colonial and post-colonial era Indigenous sites have similar issues (e.g. McNiven et al, 2017;Wallis and Collins, 2013;Wallis et al, 2017). Our results, therefore, provide a successful proof of concept for using quartz OSL to date anthropogenic sediments at archaeological sites of the colonial era (i.e.…”
Section: Resultssupporting
confidence: 55%
“…A complex of Aboriginal stone houses located near the Georgina River in south‐west Queensland has been mapped but not excavated (Wallis et al . ). Excavations of stone houses in south‐west Victoria and High Cliffy Island indicate use immediately before (determined through radiocarbon dating) and/or during the early years of European contact (determined through the presence of metal and glass artefacts) (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…However, Wallis et al . (: 6) rightly point out that insufficient data are available in McDonald and Berry () to assess whether or not the c.8000‐year‐old midden deposits are contemporaneous with or predate stone house construction on Rosemary Island. Understanding the nature of stone house deposits and the chronology of occupation are far from simple exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in Queensland Kreij et al (2018) have explored stone fish traps in the Gulf of Carpentaria, Fitzpatrick et al (2018) have investigated stone arrangements on Lizard Island and Barker et al (2016) have documented stone arrangements on Mine Island. In this same vein, Wallis et al (2017) reported on huts near the Marion Downs Station airstrip, about 60 km southwest of the township of Boulia in the traditional lands of the Pitta-Pitta people. Initially documented by Davidson et al (1989), these circular structures all have substantial bases of stones and sometimes their interiors retain elements of collapsed wooden superstructure.…”
Section: Introductionmentioning
confidence: 89%
“…Initially documented by Davidson et al (1989), these circular structures all have substantial bases of stones and sometimes their interiors retain elements of collapsed wooden superstructure. They were argued by Wallis et al (2017) to have been domestic structures built by Aboriginal people to a deliberate pattern, being positioned to afford protection from inclement weather.…”
Section: Introductionmentioning
confidence: 99%